The Influence of Using #ACAB on Platform X as a Form of Hashtag Activism on Students' Trust in Mainstream Media - Zikri Fachrul Nurhadi; Azahar Kasim; Indriani (Yayasan Sinergi Kawula Muda, 2026)
This research is motivated by the increasing use of social media as a space for public criticism, particularly through hashtag activism practices such as the use of the hashtag #ACAB on platform X, which has the potential to influence how students assess the credibility of mainstream media in reporting sensitive issues. The purpose of this study is to examine the relationship between the use of the hashtag #ACAB on platform X and the level of student trust in mainstream media. This research method uses a descriptive method with a quantitative approach. The population in this study were active students who use platform X, with 21 students aged 18-23 years as the target respondents. The results of this study indicate that the level of #ACAB use on platform X is high, while the level of trust in mainstream media is low. The results of the quadratic regression analysis indicate that #ACAB usage is significantly associated with students' trust in mainstream media in a non-linear U-shaped relationship, with a contribution of 31.6%. At low to medium levels of use, increased #ACAB use tends to decrease trust in mainstream media, but at high levels of use, the relationship reverses and tends to increase trust. The limitations of this study lie in the focus of the analysis which is only on one hashtag (#ACAB) on Platform X and on student respondents, so that the findings cannot be generalized to other platforms, different activism hashtags, or wider community groups. This study contributes to providing empirical evidence based on statistical data regarding the relationship between variables, which can serve as a reference for developing quantitative studies in communication and media studies.